FOTOGRAFER DAN RISET Pcntingnya Riset dalam Fotografi - Prayanto WH. (Ars: Jurnal Seni Rupa dan Desain, 2007)
W1ien an audience observes a picture or photograph, the resulting opinions might be varied, suchas that a picture is good or interesting; there is an emotional bond with a picture; a photograph conveysmemory, it has a story or a specific message. Basically, photography is a communicative medium since aphoto possesses a communicative value when it is used to deliver a message, or when it is an idea expressedto an audience so that there will be a similar understanding «> /0 its meaning When the “expressiono f the photo" is not clcar, not only its meaning but also its objective as well as the message it deliverswould be unclear - which means the communicative process does not work as it is supposed to. In orderto effectively express a message through a photo, in addition to obtaining a go a l idea, an appropriateand contextual "structure of photographic language' should be applied. This "structure o f photographiclanguage" includes the application o f technique, lighting and appropriate composition (aesthetics)In addition to possessing and mastering the above skills, it is necessary for a photographer to beaware o f undertaking research before conducting a photography session. Conducting research provides boththe photographer and also others interested in the photo with several advantages. It not only enables aphotographer to obtain good, interesting and beautiful photos, but the photo session will also be more effectiveand efficient because of this research. No matter how simple is the reason for conducting a photographysession; research should be earned out. Conducting research for photography - fo r aspects o f idea, techniqueas well as aesthetics - can encompass the problem o f identification, analysis, and developing a conclusionprior to the execution o f the photography session.Keywords: photography, photographer, research